2018
DOI: 10.1108/ijlma-03-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

The effect of managerial and institutional ownership on corporate social responsibility disclosure

Abstract: Purpose This study aims to analyze the effect of ownership structure that consists of managerial ownership and institutional ownership of the extensive of corporate social responsibility (CSR) disclosure. Design/methodology/approach The population in this study is manufacturing companies listed in Indonesia Stock Exchange (BEI), as the manufacturing companies are considered to have great potential on environmental damage (Mathews, 2000). The selected sample were the companies which meet certain criteria (pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
1
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 24 publications
6
54
1
20
Order By: Relevance
“…According to Nurleni et al (2018), the high proportion of administrative ownership could provide bank executives with greater incentive to reduce their banks' exposure to risk and maximize the value of these banks. This articulation is supported by Aebi et al (2012), who have reported empirical evidence that higher administrative ownership reduces the risky decisions in banks and increases the level of their financial stability.…”
Section: Administrative Ownershipmentioning
confidence: 99%
“…According to Nurleni et al (2018), the high proportion of administrative ownership could provide bank executives with greater incentive to reduce their banks' exposure to risk and maximize the value of these banks. This articulation is supported by Aebi et al (2012), who have reported empirical evidence that higher administrative ownership reduces the risky decisions in banks and increases the level of their financial stability.…”
Section: Administrative Ownershipmentioning
confidence: 99%
“…A review of prior studies that evaluated the CSR disclosures of companies revealed that a majority of these studies focused primarily on the quantity of disclosures provided in company annual reports (e.g., Bhatia & Chander, 2014;Cahan et al, 2016;Ali et al, 2017;Nurleni & Bandang, 2018;Wasiuzzaman & Wan Mohammad, 2020). Other studies focused on the quality of CSR disclosures provided by companies (e.g., Chauvey et al, 2015;Noronha et al, 2015;Muttakin & Subramaniam, 2015).…”
Section: Csr Disclosuresmentioning
confidence: 99%
“…Over the last few decades, the issue of corporate social responsibility (CSR) has transitioned from something companies did out of a sense of charity to something absolutely crucial to business survival as stakeholders demand more than just goods and services from these companies (Nurleni & Bandang, 2018). The concept of triple bottom line where companies have to concern themselves with profits, CSR constitutes the commitment shown by companies to contribute to the economic and social development of the society.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini merupakan pengembangan dari penelitian sebelumnya oleh Nurleni, Bandang, Darmawati & Amiruddin (2018). Perbedaan penelitian ini dengan penelitian sebelumnya adalah: 1.…”
unclassified